Data Deprivation: Another Deprivation to End - Serajuddin, Umar (World Bank E-Library Archive, 2015)
The Millennium Development Goal of halving the incidence of extreme poverty from its 1990 level will be achieved in 2015, and the international development community is now moving to a new goal of "ending extreme poverty." However, the data needed to monitor progress remain severely limited. During the 10 year period between 2002 and 2011, as many as 57 countries have zero or only one poverty estimate. This paper refers to such lack of poverty data as "data deprivation," because the poor are often socially marginalized and voiceless, and the collection of objective and quantitative data is crucial in locating them and formulating policy to help them exit extreme deprivation. This paper studies the extent of data deprivation and proposes targets for ending data deprivation by 2030-the year by when the international community aims to end extreme poverty. According to the analysis in this paper, this target is ambitious but possible, and achieving it is necessary to be able to declare the end of extreme poverty with confidence